Preparation method of low-thermal-conductivity porous carbon-based high-temperature-resistant adhesive pre-impregnated adhesive film
By forming a low-thermal conductivity porous carbon-based structure in a high-temperature resistant adhesive, the problem of the increase in thermal conductivity of the existing high-temperature resistant adhesive after graphitization of carbide is solved, and the effect of maintaining strength at high temperature and reducing thermal conductivity is achieved, which is suitable for insulation and heat insulation under ultra-high temperature conditions.
Patent Information
- Application Number
- CN202510023572.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
The thermal conductivity of existing high-temperature resistant adhesives increases after graphitization of carbide, which cannot meet the thermal insulation requirements under ultra-high temperature conditions.
Through a specific preparation process, a low-thermal conductivity porous carbon-based high-temperature resistant adhesive prepreg film is formed, and modified phenolic resin and ash-free adhesive absorbing felt are used. After curing, carbonizing and graphitizing, a complex high-residue carbon pore wall structure and a large number of network pore carbon structures are formed.
It realizes the effective reduction of thermal conductivity while maintaining good bonding strength at high temperatures, meeting the insulation requirements under ultra-high temperature conditions, and is suitable for standardized and standardized production.
Smart Images

Figure CN119799190A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon material thermal insulation adhesives, and in particular to a method for preparing a low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film. Background Art
[0002] Carbon materials are mainly composed of carbon, with a carbon content of more than 99%. Due to their high temperature stability, excellent thermal conductivity, good thermal shock resistance and corrosion resistance, they are widely used in metallurgy, chemistry, electronics, aerospace and other fields. Among them, high-temperature carbon materials such as graphite products, carbon bricks and carbon fiber composites can maintain physical and chemical stability in extremely high temperature environments.
[0003] In the processing and application of carbon materials, interlayer bonding is a key step. However, although commonly used high-temperature adhesives can maintain good adhesion at high temperatures, their high carbon residue and dense carbon layer structure lead to increased thermal conductivity, making bonding strength and thermal insulation performance a pair of contradictions that are difficult to balance. In addition, common high-temperature adhesives are prone to seepage and loss at high temperatures, and need to be used excessively to ensure the bonding effect, which not only increases costs, but also further increases thermal conductivity and leads to different performance standards for each batch of products.
[0004] Therefore, it is particularly important to develop a carbon-based material interlayer adhesive that can maintain high bonding strength, effectively reduce thermal conductivity, and can be produced in a standardized and regular manner. Summary of the invention
[0005] In view of the fact that although the existing high-temperature resistant adhesives have good bonding properties, there are not enough pores or holes after carbonization and graphitization, which leads to increased thermal conductivity and cannot meet the problem of thermal insulation under ultra-high temperature conditions. The present invention aims to provide a method for preparing a low-thermal-conductivity porous carbon-based high-temperature resistant adhesive prepreg film. Through a specific preparation process, the adhesive forms an intricate high-residual carbon pore wall structure at high temperature. A large number of network pore carbon structures effectively reduce the thermal conductivity while ensuring good bonding strength.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The object of the present invention is to provide a method for preparing a low thermal conductive porous carbon-based high temperature resistant adhesive prepreg film, comprising the following steps:
[0008] Step 1: Material preparation
[0009] At room temperature, 18 to 60 parts of modified phenolic resin are impregnated in ashless adhesive felt. The phenolic resin is preferably etherified phenolic resin, aminophenolic resin, barium phenolic resin or sodium phenolic resin, which have excellent high temperature resistance and adhesion. The ashless adhesive felt can be made of polyester fiber felt, polyacrylonitrile felt, polyethylene felt or nylon felt, with a thickness of 0.2 to 3 mm and a mass of 40 to 200 g / m 2 After impregnation, polyethylene isolation films are laid on the upper and lower surfaces of the adhesive felt, and the felt is stored for a long time at -30℃~-5℃ by low-temperature freezing method to prevent the material from deteriorating.
[0010] Step 2: Curing
[0011] The impregnated and preserved adhesive felt is laid flat to bond the carbon material to form an intermediate. Then, the intermediate is placed in a curing furnace and heated to 150°C to 300°C at a heating rate of 5 to 30°C / h. After being kept in this temperature range for 1 to 4 hours, it is taken out after being naturally cooled to room temperature. The curing treatment allows the phenolic resin to be tightly combined with the adhesive felt and the carbon material to form a stable structure.
[0012] Step 3: Carbonization
[0013] The solidified intermediate is placed in a vacuum carbonization furnace and heated to 850℃~1100℃ at a heating rate of 5~50℃ / h. After keeping the temperature within this temperature range for 1~4h, it is taken out after being cooled naturally to room temperature. The carbonization treatment converts the organic matter in the material into carbon, forming a porous structure and reducing the thermal conductivity.
[0014] Step 4: Graphitization
[0015] The carbonized intermediate is placed in a vacuum graphitization furnace and heated to 1800℃~2400℃ at a heating rate of 5~50℃ / h. After being kept in this temperature range for 1~4h, it is taken out after being cooled naturally to room temperature. The graphitization treatment further graphitizes the carbon material and improves the high temperature resistance and stability of the material.
[0016] The present invention relates to a pre-impregnated film of a low-thermal-conductivity porous high-temperature-resistant adhesive between carbon material layers, wherein the adhesive felt is cracked and volatilized at high temperature, and the phenolic resin is formed into an intricate high-carbon residual pore wall structure at high temperature, and a large number of network pore carbon structures make the high-temperature bonding effect better, and take into account the lower thermal conductivity. More importantly, the use of the form of a pre-impregnated film, on the one hand, will reduce the flow of phenolic resin, and better bond with carbon materials. On the other hand, the pre-impregnated film can achieve standardized and standardized production process requirements, so that the product specifications are standard, have good structural processability, and meet quality standards, thereby solving the problem that although the existing high-temperature resistant adhesive has good bonding performance, there are not enough pores or holes after carbonization and graphitization, resulting in an increase in thermal conductivity, and it cannot meet the requirements of thermal insulation under ultra-high temperature conditions.
[0017] The present invention prepares phenolic resin and adhesive felt in a certain mass ratio to form a pre-impregnated film. After the pre-impregnated film is laid flat between the carbon-based material layers, the low thermal conductivity porous adhesive felt pre-impregnated film between the carbon material layers reacts and solidifies during the curing process to form a resin bonding layer with a large number of holes or pores, and then during the carbonization and graphitization process, the adhesive felt decomposes into intricate channels and prompts the resin bonding layer to form a carbonized bonding layer with high residual carbon, and maintains sufficient holes or pores, thereby achieving excellent bonding performance and maintaining good thermal insulation performance. The low thermal conductivity porous high temperature resistant adhesive pre-impregnated film method proposed by the present invention has cheap and easy-to-obtain raw materials, and has the remarkable characteristics of high residual carbon rate, low smoke emission, low toxicity, etc. The production process is simple, and the standard and standardized pre-impregnated film makes the product specification standard, has good structural processability, and meets the quality standards.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. Through specific preparation steps and material selection, the low thermal conductivity and porous structure of the adhesive prepreg film are achieved while maintaining its high temperature resistance.
[0020] 2. During the preparation process, low-temperature freezing, vacuum carbonization and graphitization treatment are used to improve the quality and stability of the product.
[0021] 3. The adhesive prepreg film of the present invention is suitable for various fields requiring high-temperature bonding and low thermal conductivity and heat preservation effects, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of some key steps in the preparation process of low thermal conductivity porous high temperature resistant adhesive prepreg film
[0023] Figure 2 Schematic diagram of the preparation process of low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film
[0024] Figure 3 It is a low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film with low temperature thermal conductivity
[0025] Figure 4 It is a low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film with high temperature thermal conductivity
[0026] Figure 5 The tensile shear bonding force and bonding strength of the carbon material after carbonization of the low thermal conductivity porous carbon-based high temperature resistant adhesive pre-impregnated film
[0027] Figure 6 This is a SEM photo of a common high-temperature adhesive after carbonization.
[0028] Figure 7 This is the SEM photo of the low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film after carbonization DETAILED DESCRIPTION
[0029] Embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although certain embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present disclosure. It should be understood that the drawings and embodiments of the present disclosure are only for exemplary purposes and are not intended to limit the scope of protection of the present disclosure.
[0030] It should also be noted that, for ease of description, only the parts related to the relevant inventions are shown in the drawings. In the absence of conflict, the embodiments in this disclosure and the features in the embodiments can be combined with each other. The embodiments are only a part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work should fall within the scope of protection of this application.
[0031] Example 1
[0032] like Figure 1-2 As shown, at room temperature, the modified barium phenolic resin was impregnated into a 0.2 mm thick, 45 g / m 2of polyester fiber adhesive felt. After impregnation, polyethylene isolation film is laid on the upper and lower surfaces of the adhesive felt, and it is stored by low-temperature freezing method at -30℃~-5℃. Then, the impregnated and stored adhesive felt is laid flat to bond the carbon material to form an intermediate. The intermediate is placed in a curing furnace, heated to 150℃ at a heating rate of 5℃ / h, and kept at this temperature for 1h, and then it is naturally cooled and taken out. Next, the cured intermediate is placed in a vacuum carbonization furnace, heated to 850℃ at a heating rate of 5℃ / h, and kept at this temperature for 1h, and then it is naturally cooled and taken out. Finally, the carbonized intermediate is placed in a vacuum graphitization furnace, heated to 1800℃ at a heating rate of 5℃ / h, and kept at this temperature for 2h, and then it is naturally cooled and taken out to obtain a low thermal conductivity porous carbon-based high temperature resistant adhesive carbon material.
[0033] Example 2
[0034] like Figure 1-2 As shown, at room temperature, 25 parts of modified phenol-formaldehyde resin were impregnated into a 0.8 mm thick, 95 g / m 2 of polyacrylonitrile felt. After impregnation, polyethylene isolation film is laid on the upper and lower surfaces of the felt, and it is preserved by low-temperature freezing method at -30℃~-5℃. Then, the impregnated and preserved felt is laid flat to bond the carbon material to form an intermediate. The intermediate is placed in a curing furnace, heated to 200℃ at a heating rate of 10℃ / h, and kept at this temperature for 2h, and then it is naturally cooled and taken out. Next, the cured intermediate is placed in a vacuum carbonization furnace, heated to 950℃ at a heating rate of 10℃ / h, and kept at this temperature for 2h, and then it is naturally cooled and taken out. Finally, the carbonized intermediate is placed in a vacuum graphitization furnace, heated to 1900℃ at a heating rate of 10℃ / h, and kept at this temperature for 2h, and then it is naturally cooled and taken out to obtain a low thermal conductivity porous carbon-based high temperature resistant adhesive carbon material.
[0035] Example 3
[0036] like Figure 1-2 As shown, at room temperature, 30 parts of modified sodium phenolic resin were impregnated into a 1.5 mm thick, 140 g / m 2In the polyethylene adhesive felt. After impregnation, polyethylene isolation film is laid on the upper and lower surfaces of the adhesive felt, and it is preserved by a low-temperature freezing method at -30℃~-5℃. Then, the impregnated and preserved adhesive felt is laid flat to bond the carbon material to form an intermediate. The intermediate is placed in a curing furnace, heated to 250℃ at a heating rate of 15℃ / h, and kept at this temperature for 3h, and then it is naturally cooled and taken out. Next, the cured intermediate is placed in a vacuum carbonization furnace, heated to 1000℃ at a heating rate of 20℃ / h, and kept at this temperature for 3h, and then it is naturally cooled and taken out. Finally, the carbonized intermediate is placed in a vacuum graphitization furnace, heated to 2000℃ at a heating rate of 20℃ / h, and kept at this temperature for 3h, and then it is naturally cooled and taken out to obtain a low thermal conductivity porous carbon-based high temperature resistant adhesive carbon material.
[0037] Example 4
[0038] like Figure 1-2 As shown, at room temperature, 45 parts of etherified phenolic resin were impregnated into a 3 mm thick, 200 g / m 2 nylon 66 adhesive felt. After impregnation, polyethylene isolation film is laid on the upper and lower surfaces of the adhesive felt, and it is preserved by low-temperature freezing method at -30℃~-5℃. Then, the impregnated and preserved adhesive felt is laid flat to bond the carbon material to form an intermediate. The intermediate is placed in a curing furnace, heated to 300℃ at a heating rate of 5℃ / h, and kept at this temperature for 4h, and then it is naturally cooled and taken out. Next, the cured intermediate is placed in a vacuum carbonization furnace, heated to 1100℃ at a heating rate of 35℃ / h, and kept at this temperature for 4h, and then it is naturally cooled and taken out. Finally, the carbonized intermediate is placed in a vacuum graphitization furnace, heated to 2100℃ at a heating rate of 40℃ / h, and kept at this temperature for 4h, and then it is naturally cooled and taken out to obtain a low thermal conductivity porous carbon-based high temperature resistant adhesive carbon material.
[0039] The phenolic resins in Examples 1-4 are etherified phenolic resin, aminophenolic resin, barium phenolic resin, and sodium phenolic resin; the ash-free adhesive felts are polyester fiber felt, polyacrylonitrile felt, polyethylene felt, and nylon 66 felt; all the ash-free adhesive felts have a thickness of 0.2 to 3 mm and a mass of 40 to 200 g / m 2 .
[0040] Product performance test results such as Figure 3-7 As shown:
[0041] like Figure 3As shown in the figure, the thermal conductivity of common high-temperature adhesives after carbonization at 90°C is 1.9467W (m·K), the thermal conductivity of Example 1 is 1.3213W (m·K), the thermal conductivity of Example 2 is 1.4391W (m·K), the thermal conductivity of Example 3 is 1.6672W (m·K), and the thermal conductivity of Example 4 is 1.2433W (m·K). The data show that low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film can reduce thermal conductivity.
[0042] like Figure 4 As shown in the figure, the thermal conductivity of common high temperature adhesives at 1550℃ is 0.2847W(m·K), the thermal conductivity of Example 1 is 0.2659W(m·K), the thermal conductivity of Example 2 is 0.2721W(m·K), the thermal conductivity of Example 3 is 0.2732W(m·K), and the thermal conductivity of Example 4 is 0.2689W(m·K). The data show that the low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film can reduce high temperature thermal conductivity.
[0043] like Figure 5 As shown in the figure, the tensile shear strength of common high temperature adhesives is 3.3042 kPa, the tensile shear strength of Example 1 is 6.9161 kPa, the tensile shear strength of Example 2 is 12.2930 kPa, the tensile shear strength of Example 3 is 13.7074 kPa, and the tensile shear strength of Example 4 is 8.9087 kPa. The data show that the low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film can improve the tensile shear strength.
[0044] like Figure 6 As shown in the figure, the microstructure morphology of common high-temperature adhesives after carbonization has a smooth surface and a large contact area, thereby improving the thermal conductivity of the material.
[0045] like Figure 7 As shown, the carbonized microstructure morphology of the low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film has micron-sized pores on the surface, which reduces the contact area, conduction and convection, thereby reducing the thermal conductivity of the material.
[0046] It can be seen from the product performance tests of Examples 1-4 that the method of the present invention can effectively prepare a prepreg film with excellent high-temperature bonding performance and low thermal conductivity and heat preservation effect. The method forms a complex pore wall structure through the high-temperature pyrolysis and volatilization of the adhesive felt and the high carbon residue rate of the phenolic resin, which significantly reduces the thermal conductivity. At the same time, the use of the prepreg film reduces the flow of the phenolic resin, realizes standardized and standardized production, and ensures the high quality and high consistency of the product.
[0047] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0048] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0050] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film, characterized in that: The following steps are involved: Step 1: Material preparation At room temperature, 18 to 60 parts of modified phenolic resin are impregnated into ash-free adhesive felt, polyethylene isolation films are laid on the upper and lower surfaces, and the felt is stored at -30°C to -5°C for a long time by a low-temperature freezing method; Step 2: Curing The adhesive felt is laid flat to bond the carbon material to form an intermediate, which is placed in a curing furnace and heated to 150°C to 300°C at a heating rate of 5 to 30°C / h. After being kept in this temperature range for 1 to 4 hours, it is taken out after being cooled naturally. Step 3: Carbonization After the solidified intermediate is placed in a vacuum carbonization furnace, it is heated to 850°C to 1100°C at a heating rate of 5 to 50°C / h, kept in this temperature range for 1 to 4 hours, and then taken out after being cooled naturally; Step 4: Graphitization The carbonized intermediate is placed in a vacuum graphitization furnace and heated to 1800°C to 2400°C at a heating rate of 5 to 50°C / h. After being kept within the temperature range for 1 to 4 hours, it is naturally cooled and taken out.
2. The method for preparing a low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film according to claim 1, characterized in that: The ash-free adhesive felt described in step one includes at least one of polyester fiber felt, polyacrylonitrile felt, polyethylene felt or nylon felt.
3. The method for preparing a low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film according to claim 2, characterized in that: The thickness of the ash-free adhesive felt is 0.2-3 mm.
4. The method for preparing a low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film according to claim 3, characterized in that: The mass of the ash-free adhesive felt is 40 to 200 g / m 2 .
5. The method for preparing a low thermal conductivity porous carbon-based high temperature resistant adhesive prepreg film according to claim 1, characterized in that: The modified phenolic resin in step 1 includes at least one of etherified phenolic resin, aminophenolic resin, barium phenolic resin or sodium phenolic resin.